Syntheses and characterizations of the cyanide-bridged heteronuclear polymeric complexes with 2-ethylimidazole - D. Karaağaç; G. S. Kürkçüoğlu (Bulletin of the Chemical Society of Ethiopia, 2016)
Three new cyano-bridged heteronuclear polymeric complexes, [Cu(etim)3Ni(CN)4]n, {[Zn(etim)3Ni(CN)4]∙H2O}n and [Cd(etim)2Ni(CN)4]n (etim = 2-ethylimidazole, hereafter abbreviated as Cu–Ni–etim, Zn–Ni–etim and Cd–Ni–etim) have been prepared in powder form and characterized by FT-IR and Raman spectroscopies, thermal (TG, DTG and DTA) and elemental analyses. The spectral features of the complexes suggest that the Ni(II) ion is four coordinate with four cyanide-carbon atoms in a square planar geometry, whereas the Cu(II) and the Zn(II) ions of the Cu–Ni–etim and the Zn–Ni–etim complexes are completed by nitrogen atoms of two cyano groups of [Ni(CN)4]2- coordinated to the adjacent M(II) ions and three nitrogen atoms of the etim ligands. The Cd(II) ion of the Cd–Ni–etim complex is six-coordinate, completed with the two nitrogen atoms of the etim ligands and the four nitrogen atoms from bridging cyano groups. Polymeric structures of the Cu–Ni–etim and the Zn–Ni–etim complexes are 1D coordination polymer, while complex the Cd–Ni–etim presents a 2D network. The thermal decompositions in the temperature range 30–700 °C of the complexes were investigated in the static air atmosphere.